Vitamin D Deficiency and its Clinical Manifestations in Young Adults Attending General OPDs - HARAL, AYESHA HARAL; HAYAT, TEHREEM HAYAT; BATOOL, RAMSHA BATOOL; ASGHAR, RABEEZA ASGHAR; SHEHZAD, VISHA SHEHZAD; GHAFFAR, FATIMA GHAFFAR; FAISAL, AMNA FAISAL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Vitamin D deficiency is a growing global health problem affecting not only older adults but also younger populations. Despite adequate sunlight in Pakistan, low vitamin D levels remain prevalent, mainly due to indoor lifestyles, limited dietary intake, and cultural factors. Objective: To determine the prevalence and clinical manifestations of vitamin D deficiency among young adults attending general outpatient departments (OPDs) of two tertiary-care hospitals in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted from January 2024 to March 2025 at Ghurki Trust Teaching Hospital and University of Lahore Teaching Hospital. A total of 150 participants aged 18–35 years were enrolled through non-probability consecutive sampling. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured using a chemiluminescent immunoassay. Participants were categorized as deficient (<20 ng/mL), insufficient (20–30 ng/mL), or sufficient (>30 ng/mL). Clinical symptoms, sunlight exposure, and dietary habits were assessed through structured interviews. Results: Vitamin D deficiency was detected in 62.7% of participants, insufficiency in 24%, and sufficiency in 13.3%. Deficiency was significantly higher in females (70%) and those with indoor occupations (71.9%). The most frequent symptoms included generalized body aches (56%), fatigue (45%), and bone pain (33%). Lower vitamin D levels were strongly associated with reduced sunlight exposure and poor intake of vitamin D–rich foods (p < 0.05). Conclusion: Vitamin D deficiency is alarmingly common among young adults in Lahore, frequently presenting with vague musculoskeletal complaints. Early screening, improved sunlight exposure, and dietary fortification are essential preventive strategies to reduce deficiency-related morbidity.